ON THE ROLE OF ATP-DEPENDENT POTASSIUM CHANNEL Kir6.2 AND HYPOXIA-INDUCED FACTOR-1α IN THE PENTYLENETETRAZOLE KINDLING PATHOGENESIS - Doganyigit, Z.; Okan, A.; Akyuz, E.; Poshyvak, O.B.; Pervak, M.P.; Yehorenko, O.S.; Hathal, S.N.A. (World of Medicine and Biology, 2022)
The purpose of the study was the immunohistochemical examination of the expression of the ATP-sensitive potassium (K+) channel Kir6.2 and hypoxia-inducible factor 1α in the dorsal hippocampus in kindled rats. Kindling was produced in 19 rats by the three-week pentylenetetrazole administration. The avidin-biotin-peroxidase method was used in 10 control rats for staining. The rest 10 rats were composed of the negative control and stained using only secondary antibodies. The colour intensity of the brain sections of the control and kindling groups was compared with one of the negative control. In rats with pentylenetetrazole kindling, the level of Kir6.2 was 18.12+0.98 relative units and exceeded the corresponding data in control (7.53+0.72 relative units), (p